2019
DOI: 10.28933/ijprr-2019-09-2105
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of optimism and resilience on emotional distress in infertility: an integrative literature review

Abstract: Review Article IJPRR (2019) 2:22 Objective: To find any role of optimism and/or resilience mediating emotional distress in infertility. Method: We performed a literature search for 2000-2017 in PubMed, PsycINFO and Elsevier, for original articles and reviews, using keywords "resilience," "infertility," "optimism," "LOT-R," "in vitro fertilization," and "assisted reproductive technology." Additional references were collected from articles located thereby. Results: The evidence reveals a growing trend of promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
(112 reference statements)
1
5
0
Order By: Relevance
“…This is supported by the opinion of previous research, which stated that individuals with low optimism are at risk for poor mental health in the long term (Mangestuti et al, 2020). The control possessed by individuals in the absence of optimism tends not to be able to help individuals survive difficult periods (Roellyana & Listiyandini, 2016;Santa-Cruz et al, 2019). Low optimism also triggers a cycle of grief including depression, anxiety, relationship problems, and a worsening quality of life.…”
Section: Discussionmentioning
confidence: 68%
“…This is supported by the opinion of previous research, which stated that individuals with low optimism are at risk for poor mental health in the long term (Mangestuti et al, 2020). The control possessed by individuals in the absence of optimism tends not to be able to help individuals survive difficult periods (Roellyana & Listiyandini, 2016;Santa-Cruz et al, 2019). Low optimism also triggers a cycle of grief including depression, anxiety, relationship problems, and a worsening quality of life.…”
Section: Discussionmentioning
confidence: 68%
“…In the present research, we found that although women perceived an overall negative impact of the COVID-19 pandemic on their fertility treatment and experienced various negative emotions as a result, women who were higher in trait optimism had fewer negative perceptions and emotions. Although trait optimism has previously been associated with less distress in women with fertility problems (e.g., [ 25 ]), this is the first study to show that optimism is associated with less distress in the crux of an additional novel stressor, including one that has threatened access to treatment. Future research should examine questions such as whether trait optimism is associated with better responses to treatment following the pandemic or how clinicians can cultivate optimism with their patients during novel stressful times.…”
Section: Discussionmentioning
confidence: 80%
“…In the area of pregnancy and fertility, trait optimism has similarly been found to be helpful when experiencing stressful feelings (e.g., [ 23 ]). In women dealing with fertility problems, at least two reviews of the literature have highlighted trait optimism as an important factor that can reduce high distress (e.g., [ 24 , 25 ]). Higher optimism has also been associated with less anxiety when women with fertility problems undergo treatment that ultimately fails [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a patient under fertility treatment without impaired resilience has a high probability of not demonstrating “Renewed elevation of distress” or “Low self‐esteem.” The inability to conceive has been described to be deeply rooted in social standards of parenthood inducing a sense of incomplete womanhood and manhood if an individual cannot generate their own offspring (Romeiro et al., 2017; Romeiro & Caldeira, 2019). Evidence has suggested that in efforts of the couples to have a child, psychological distress and spiritual distress are triggered with resilience playing a key role in mediating emotional and spiritual processes in individuals facing infertility (Li et al., ;2019 Romeiro et al., 2017; Santa‐Cruz et al., 2019).…”
Section: Discussionmentioning
confidence: 99%